2009
DOI: 10.1007/s10856-009-3961-4
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite bone substitutes developed via replication of natural marine sponges

Abstract: The application of synthetic cancellous bone has been shown to be highly successful when its architecture mimics that of the naturally interconnected trabeculae bone it aims to replace. The following investigation demonstrates the potential use of marine sponges as precursors in the production of ceramic based tissue engineered bone scaffolds. Three species of natural sponge, Dalmata Fina (Spongia officinalis Linnaeus, Adriatic Sea), Fina Silk (Spongia zimocca, Mediterranean) and Elephant Ear (Spongia agaricin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 33 publications
0
57
0
Order By: Relevance
“…Based on the pore size, these product materials could be applied in neovascularization or attracting cell adhesion and helping cell in growth. 7), 15) The cell viability of sea urchin shell was tested by using MG-63 cells. It was found that the raw powder of sea urchin shell and its hydrothermal reaction product had no negative effect on MG-63 cells.…”
Section: )22)mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the pore size, these product materials could be applied in neovascularization or attracting cell adhesion and helping cell in growth. 7), 15) The cell viability of sea urchin shell was tested by using MG-63 cells. It was found that the raw powder of sea urchin shell and its hydrothermal reaction product had no negative effect on MG-63 cells.…”
Section: )22)mentioning
confidence: 99%
“…6) At the very least a scaffold should have sufficient stability to maintain its architecture during in vitro culturing and handling throughout implantation. 7) HA and other calcium derivatives (TCP, etc.) are the most commonly used calcium phosphates, due to their calcium/phosphorus (Ca/P) ratios bring close to that of natural bone and their stability being high when in contact with physiological environment.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, three sponges from the genus Spongia (S. officinalis, S. zimocca, and S. agaricina) were used as precursors, or templates, to produce porous HA scaffolds by a replication technique (Cunningham et al, 2010). Of the three sponges examined, Spongia agaricina produced the most promising replicated scaffold for bone tissue engineering as it had approximately 60% porosity with pore sizes in the range of 100-500 m and 99.9% interconnectivity (figure 1).…”
Section: Poriferamentioning
confidence: 99%
“…The new generation (third) of bioactive glass and foams with high macroporosity, creates a framework for penetration and migration of cells through scaffold. Using these structures act as a pattern for bone growth in the three dimensions and stimulate tissue regeneration by activating genes [23][24][25]. The porous size plays a key role in design of scaffold and directly affects bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Size of 15-40 µm allows the growth of fibroblast, 40-100 µm is appropriate for osteoid growth, 200-350 µm allows significant growth of bone and higher than 500 µm allows quick angiogenesis. According to different studies, the optimal size for osteoconductivity is 150-600 µm [25]. The mechanical properties of scaffold should provide sufficient mechanical stability before the regeneration of new tissue in areas under load [11].…”
Section: Introductionmentioning
confidence: 99%